Hydrological Response Of Unsaturated Granitic Residual Soil Slope Due To Different Rainfall Amounts And Slope Angle - Hamzah, Nur Hasliza (2017)
The aim of this study is to investigate the effect of different applied rainfall rate and slope angle on the hydrological response of unsaturated soil slope. This study involved the granitic residual soil characterization and 2D physical slope model experiments. Soil characterizations included in this study are in-situ and laboratory soil tests which was conducted on the river sand (SW) and granitic residual soil (SC) obtained from the USM Main Campus, Penang Island. The 2D physical slope model experiment is conducted with the rainfall simulator system, Time Domain Reflectometry (TDR) and tensiometer-transducer system to analyze the significance of soil properties in terms of hydrological responses which are soil suction and water content. The amount of rainfall infiltration and surface runoff were also measured by the end of the experiment. The amount of rainfall infiltrated into the soil and became surface runoff with difference applied rainfall rate and slope angles can be estimated. By conducted 2D physical slope model, it was found that the percentage for water infiltration and soil moisture content were slightly different, but substantially different in surface runoff when the soil slope angle increased between river sand (SW) and granitic residual soil (SC). Two difference value of applied rainfall rate used in this study is based on the data from rainfall intensity recorded by the rainfall station in Air Itam, Penang. The rainfall data are converted by using the flow rate, Q equation (details can be referred in section 3.4.7.1). During the applied rainfall rate of 9.78×10-9m/s and 1.66×10-9m/s, the minimum surface runoff for river sand (SW) recorded are 15.7% and 9.2% whereas the maximum surface runoff are 28.9% and 25.9% respectively. As for granitic residual soil (SC), the minimum surface runoff recorded are 30% and 30.19%, while the maximum surface runoff are 54% and 50.06% of applied rainfall rate of 9.78×10-9m/s and 1.66×10-9m/s respectively. Based on the results of both river sand (SW) and granitic residual soil (SC), the equations related to water infiltration, surface runoff and soil water content are obtained. For river sand (SW), the equations of water infiltration, surface runoff and soil moisture content are recorded as y = 43.78x-0.408, y = 16.47x0.4389 and y = 37.737x-0.712 during the applied rainfall rate of 9.78×10-9m/s while during 1.66×10-9m/s the equations are recorded as y = 45.218x-0.316, y = 9.9649x0.7318 and y = 23.091x-0.382. For granitic residual soil (SC), the equations of water infiltration, surface runoff and soil moisture content during applied rainfall rate of 9.78×10-9m/s are recorded as y = 42.582x-0.493, y = 28.254x0.4409 and y = 34.945x-0.314 while y = 40.633x-0.386, y = 29.754x0.3589 and y = 35.62x-0.384 during 1.66×10-9m/s applied rainfall rate. By measured the amount of the rainfall seeped into the soil and became surface runoff, it was found that both soils decrease water infiltration and soil moisture content but increase surface runoff when slope angle increased. These proved that, as the slope angle increased more rainfall became surface runoff than infiltrated into the soil.